Translation and Validation of Modified Dental Anxiety Scale: The Nepali Version. (29th January 2017) - Giri, Jamal; Pokharel, Prabhat Ranjan; Gyawali, Rajesh; Bhattarai, Bhushan
Abstract : Introduction. For proper management of anxious dental patients it is imperative to assess their levels of dental anxiety before treatment. Modified Dental Anxiety Scale (MDAS) is the most commonly used questionnaire to assess dental anxiety. But a Nepali version of MDAS is still lacking. Hence, the objective of this study was to develop a reliable and valid Nepali version of MDAS. Materials and Methods. The English version of the MDAS was translated into Nepali following a forward and backward translation process. Following pretesting and cognitive interviewing a final version of Nepali questionnaire was obtained. One hundred and fifty patients attending Department of Orthodontics completed the Nepali version of MDAS questionnaire at their convenience. Also, patients were asked to rate their overall anxiety on a 100 mm visual analog scale (VAS). A test-retest of the questionnaire was performed with 30 patients after 2 weeks. Results. Cronbach's alpha value of the Nepali version of MDAS was 0.775. The Intraclass Correlation Coefficient between test and retest was 0.872. Spearman's correlation coefficient between the total MDAS score and VAS score was 0.838. Conclusion. The translated Nepali version of MDAS is a reliable and valid instrument to measure the dental anxiety of Nepali patients.